Habitat predicts local prevalence of migratory behaviour in an alpine ungulate. Issue 4 (24th January 2020) - Spitz, Derek B.; Hebblewhite, Mark; Stephenson, Thomas R.
Abstract: The resource hierarchy hypothesis predicts that the most important factors limiting a species' distribution act at the coarsest spatial scales. However, resource selection behaviour affords mobile organisms the opportunity to adopt a range of tactics for navigating spatial trade‐offs between competing biotic and abiotic constraints. Throughout the animal kingdom, partial migration (where some individuals migrate, and others remain resident year round) offers a pervasive example of such behavioural polymorphism. Identifying the differences between these behaviours is therefore central to understanding the conditions (habitat) needed to sustain migrant and resident populations. Here we test an extension of the resource hierarchy hypothesis. We hypothesized that rather than responding to a single limiting factor, migration and residency represent contrasting scale‐specific approaches to managing trade‐offs between forage, predation risk and severe winter conditions. Furthermore, we predicted that the distribution of habitat selected by migrants and residents is predictive of the local prevalence of migratory behaviour. To test these hypotheses, we quantified migratory status‐ (resident/migrant) and season‐specific (winter/summer) differences in resource selection by eight populations of federally endangered Sierra Nevada bighorn sheep Ovis canadensis sierrae across three spatial scales: population range, individual range and within individual range. We then integrated these spatial predictions to produce separate spatial predictions of migrant and resident winter habitat. As predicted, model selection provided strong evidence for the importance of status‐specific differences in resource selection. Residents showed stronger coarse‐scale selection for terrain associated with predator avoidance and stronger fine‐scale selection for greenness, while in migrants this pattern was reversed. Availability of migrant habitat predicted the local prevalence of migration (top model pseudo R 2 of .87). Our ability to respond to global declines of migratory species depends on improving our understanding of the conditions required to maintain migratory behaviour. Through explicitly contrasting migrant and resident behaviour, our results illustrate seasonal differences in migrant and resident habitat and how these two behaviours represent responses to different limiting conditions. Our analyses provides a novel empirical basis for assessing the local prevalence of migratory behaviour across large landscapes. Abstract : The authors present a novel approach to identifying seasonal habitat for partially migratory species. Through a case study of an endangered ungulate, they demonstrate that behavioral models accounting for migratory tactics can predict the local prevalence of migratory behavior. These methods have great potential to inform conservation priorities for migratory species.